2022
DOI: 10.31849/elsya.v4i2.8704
|View full text |Cite
|
Sign up to set email alerts
|

How First and Second Languages Influence Indonesian Students’ English as a Third Language: Transfer and Interference Analysis

Abstract: In the face of the scarcity of linguistic studies on Batak Toba language, this study tries to contribute by investigating how Batak Toba students’ local language and mother tongue’s elements are transferred to their English as a foreign language output. Specifically, this study aims to describe the transfer and interference of Batak Toba and Indonesian as first and/or second language and how they influence learners’ English as a third language. The study observed 15 English Education programme students who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…In addition, song and video are proven as the most influential media influenced the significant enhancement towards the early childhoods' English-speaking skill. This evidence is harmony with the results of the study conducted by Maro (2018); Purba (2022); Vidhiasi (2022).…”
Section: Findings and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, song and video are proven as the most influential media influenced the significant enhancement towards the early childhoods' English-speaking skill. This evidence is harmony with the results of the study conducted by Maro (2018); Purba (2022); Vidhiasi (2022).…”
Section: Findings and Discussionsupporting
confidence: 91%
“…Then, they learn Bahasa Indonesia as their L2, and they learn English as their FL. With regard to English as FL, it refers to the language that is not commonly used in their social interaction every day, thus English is usually difficult to be spoken by the early childhoods in their daily conversation (Sigirtmac & Ozbek, 2009;Shobikah, 2018;Purba, 2022). To solve this problem, most of the early childhoods learn English privately at home or learn English at a language course.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the students' first and second language interfered with their English language performance at the phonological, morphological, and syntactic levels. Moreover, it is reinforced by other study that analyses English pronunciation that is mostly interferences by the Acehnese dialect and the reason the students find it difficult to leave the Acehnese dialect when pronouncing English (Purba, 2022). The results of the study showed that students made some interferences of sounds in pronouncing stops and fricative sounds.…”
Section: Discussionmentioning
confidence: 60%
“…Interference Phonology can be a challenge in learning a second or foreign language, because the influence of the first or native language is often manifested in the production and perception of sounds in the new language. However, with proper practice and experience, speakers of a second language can overcome interference and develop skills in using the correct sounds of the language being studied (Nurhidayat, 2021;Pasaribu, 2021;Purba, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Throughout linguistic history, various theories have emerged to explore and comprehend language learning and acquisition, encompassing both first-language and second-language acquisition as a target language (Purba, 2022). Many individuals find that visually encountering new words aids in learning, particularly in the acquisition of a second language (L2) (Welby et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%